PENGARUH SUHU DAN KECEPATAN PENGADUKAN PADA PROSES PEMBUATAN SURFAKTAN NATRIUM LIGNOSULFONAT DARI TEMPURUNG KELAPA - Jhon Peri Rinaldo Sirait; Nico Sihombing; Zuhrina Masyithah (Jurnal Teknik Kimia USU, 2013)
Coconut shell is one of agricultural wastes that having low commercial value. This research is objected to use coconut shell as the base material of producing surfactant. The use of coconut shell is basically due to its content of lignin, about 29,4%. The objective of this research is to obtain isolate lignin with increasing chatalis NaOH and H2SO4 with lignin identification, the effect of temperature and agitation rate of producing surfactant. The research was done in a reactor with temperature of 100 0C, 110 0C, 120 0C, 3 hours reaction time, pH 6, 80 rpm, 90 rpm, 100 rpm agitation rate, and coconut shell as the base material. Dry coconut shell is grinded and the powder is collected to be reacted. The coconut shell powder is reacted with sodium bisulfite solution with variation in ratio of 1:0,5. The product is filtered to get filtrate and residue. The filtrate is further analyzed by using the FT-IR spectrophotometry method. From the research we get maximum purity of surfactant at sodium bisulfite with reactant ratio of 1:0,5; Speed 100 rpm and temperature 120 0C.